D
Deleted member 4993
Guest
rajshah428 said:okay so i got A = 1/3 B = 1 C = 2/3
so the general expression is 1/3x^3 + x^2 + 2/3x
so it can be written as x^3 + 3x^2 + 2x...........................No
so that is the conjecture.
now for 2c. how do you do it?
It should be:
\(\displaystyle S_n = \frac{n^3 + 3n^2 + 2n}{3} = \frac{n(n+1)(n+2)}{3}\)
now for 2c. how do you do it?
This is your problem - tell how you would approach it.
You had defined the sum to be:
\(\displaystyle S_n = \sum_{i=1}^n{i(i+1)} = \sum_{i=1}^n{\left (i^2+i\right )}\)
\(\displaystyle \sum_{i=1}^n i = ??\)
Do not wait for spoon-feeding.